Directory : Selected CARIFORUM food producer groups, buyers and service providers - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The policy actions of the APP, reflect the common priorities of the CARIFORUM region, and are so designed to increase the capabilities of regional development organizations to addres indentifield needs, one which is that of strengthening market linkages to contribute to smallholder's and SMEdevelopent